2023
DOI: 10.3390/v15020370
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Pseudorabies Virus Usage in Vaccine Development against Swine Infectious Disease

Abstract: Pseudorabies virus (PRV) is the pathogen of pseudorabies (PR), which belongs to the alpha herpesvirus subfamily with a double stranded DNA genome encoding approximately 70 proteins. PRV has many non-essential regions for replication, has a strong capacity to accommodate foreign genes, and more areas for genetic modification. PRV is an ideal vaccine vector, and multivalent live virus-vectored vaccines can be developed using the gene-deleted PRV. The immune system continues to be stimulated by the gene-deleted P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…In contrast, the advantages of recombinant virus vaccines are their predictability of response and higher efficacy [ 14 ]. Among them, PRV is a good vector for developing multivalent vaccines [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, the advantages of recombinant virus vaccines are their predictability of response and higher efficacy [ 14 ]. Among them, PRV is a good vector for developing multivalent vaccines [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, recombinant virus vaccines offer greater response predictability and higher efficacy [ 14 ]. Among them, the pseudorabies virus (PRV) is a good vector for developing multivalent vaccines [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The UL23 protein is a thymidine kinase 9 that catalyzes the synthesis of viral DNA, participates in virus replication, and the spread of the virus in the central nervous system 10 . It has been reported that PRV lacking thymidine kinase UL23 exhibits significantly reduced virulence in infected swine 11 . Therefore, Ul23 -deficient PRV does not affect the immune response and can be used for vaccine preparation 12 .…”
Section: Introductionmentioning
confidence: 99%
“…A small number of human infections with PRV have also been reported in recent years [ 15 ]. In pigs, the PRV Bartha K61 strain can trigger a wide range of humoral and cellular immune responses as well as be a safe and effective multivalent vaccine backbone [ 16 ]. Bartha K61 recombining the GP5 gene of Porcine Reproductive and Respiratory Syndrome Virus (PRRSV) has been proved to reduce pathogenic lesions caused by PRRSV infection in vaccinated pigs [ 17 ].…”
Section: Introductionmentioning
confidence: 99%